Pengembangan Multimedia Interaktif Android Pembelajaran Sistem Pengapian DLI Peserta Didik Kelas XI SMK Muhammadiyah Bligo - Setiawan, Irman; Kurniawan, Adhetya (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to develop Android-based interactive multimedia in Distributor Less Ignition System (DLI) learning to improve student learning outcomes. The research method used is research and development with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The research population included all students of class XI of SMK Muhammadiyah Bligo, with a purposive sampling technique involving two classes totaling 70 students. Data collection instruments include learning outcome tests and student response questionnaires. The results of the media feasibility test showed that the assessment by media experts was 88% and by material experts by 90%, both of which were in the